Evaluación de cerveza artesanal tipo ale con dos tipos de lúpulo y uso de mucílago de cacao (Theobroma cacao L.) como sustituto parcial de la levadura - Párraga Maquilón, Jonathan Steven (2022)
Cocoa mucilage is a rich medium for microbial development due to the presence of different sugars, water, pectin and mineral salts, helping fermentation with the presence of Saccharomyces cerevisiae, for this reason this project seeks to provide added value to this residue. that it was commonly discarded and thus contribute to the economic growth of the Rio Chila site, in the Valencia canton of the Los Ríos province. The objective of this research is to evaluate an Ale-type craft beer with two types of hops (Cascade and Northern Brewer) and the use of cocoa mucilage (Theobroma cacao L.) of the variety (Nacional and CCN-51) as a source of sugars. A design (AxBxC) was applied, the factors studied are A (cocoa varieties), B (mucilage concentration) and C (types of hops), which corresponds to 8 treatments with 3 replicates, obtaining 24 experimental units. STATGRAPHICS statistical software was used to establish statistical differences with Tukey's test. Physical chemical analysis was carried out, in which it presented values of 0.51% acidity, 5.27 °Brix, pH 4.23, absorbance 1.13, transmittance 8%, suspended solids 0.02g: 2.66%, density 1.06 g/mL, turbidity 11.27 NTU, °GL 7.93% vol., amount of foam 1.67 cm, colorimetry L* 46.55, colorimetry a* 19.31, colorimetry b* 48 .14 and degree of bitterness 29.73 pH, microbiological analysis was also carried out in which total absence of total coliforms was observed. The best experiment was determined through a sensory analysis in which 18 tasters participated in the 24 treatments, evaluating appearance, aroma, flavor and mouthfeel, in which the best National treatment + 30% concentration + Cascade providing excellent characteristics to the beer and good consumer appreciation. Keywords: Cocoa mucilage, residue, added value, concentration, craft beer